Adapted tracer gas test for passive measurement of total air change rates using alternative tracer substance. (9th August 2022) - Paralovo, Sarah Lima; Stranger, M.; Lazarov, B.; Spruyt, M.; Laverge, J.
Abstract : This paper describes the development of a new adaptation of the traditional tracer gas test (TGT) used for total air change rates (ACH) measurement. This adapted TGT, based on constant tracer injection, is intended for use in large-scale IAQ assessments and employs an alternative tracer gas that is more adequate than the currently employed SF6 and perfluorocarbons, and that can be co-captured and co-analyzed with commonly assessed VOCs by commercial passive IAQ-sampling. As it is based on passive sampling, the proposed TGT yields long-term integrated ACH values, and is thus indicated only for studies focused on characterizations based on average estimations rather than on analyses requiring fine temporal resolution. By means of literature study and lab experiments, decane-D22 was selected as a suitable tracer substance. The selected tracer was shown not to adhere/absorb significantly to surfaces. A passive source of decane-D22 was selected and optimized in lab, providing stable and repeatable emission rates unaffected by varying RH and ACH. An exponential prediction curve was derived for determining the source emission rate from the average room temperature. Moreover, a range of adequate levels of liquid tracer inside the source is suggested. A successful field test application for validation of the new TGT is also described.